Effects of pore shape and porosity on the dielectric constant of porous β-SiAlON ceramics. Issue 15 (December 2015) - Hou, Zhaoping; Ye, Feng; Liu, Limeng
Abstract: Gradient porous and homogeneous porous β-SiAlON ( Z = 2) ceramics were successfully fabricated through the unidirectional freezing of camphene-based suspensions at 0 °C and −196 °C, respectively. The dielectric constant of the porous β-SiAlON ceramics was investigated as a function of the pore shape and porosity. The dielectric constant decreased with increasing porosity, and the gradient porous β-SiAlON ceramics with channel and dendritic pores exhibited lower dielectric constants than homogeneous samples with irregular pores. The dielectric constants of the gradient porous β-SiAlON ceramics were found to be in good agreement with the prediction of the modified cubes model. The dielectric constant of the porous β-SiAlON ceramics was associated not only with porosity and pore shape, but also with pore anisotropy. The value of dielectric loss was not sensitive to porosity. These results have practical value for fabricating and optimizing porous ceramics on specific applications.